Roger William Riis papers - Riis, Roger William, 1894-
Correspondence, diaries, journal, speeches, articles and other writings, subject files, scrapbooks, pamphlets and booklets, photographs, and other papers pertaining to Riis's work as an author writing under his own name and under the pseudonym, Niel Hunter, for Reader's Digest and other publications. Subjects include fraud in automobile repair and other repairs, cigarettes and tobacco smoking, the American Civil Liberties Union, and the Sherman Act. Also includes material pertaining to his service in the U.S. Navy during World War I.
Family correspondents include Elizabeth Hipple Riis Foster, Martha Riis Moore, J. Riis Owre, and Jacob August Riis. Other correspondents include Roger Nash Baldwin, William Benton, Robert Donner, Morris Leopold Ernst, Carlton Fredericks, Arthur Garfield Hayes, John Haynes Holmes, James Rorty, George Seldes, and DeWitt Wallace.
Library of Congress Prints and Photographs Division.
Author and editor. Died 1953.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baldwin, Roger N. -- 1884-1981 -- Correspondence; Benton, William, -- 1900-1973 -- Correspondence; Donner, Robert, -- -1964 -- Correspondence; Ernst, Morris Leopold, -- 1888- -- Correspondence; Foster, Elizabeth Hipple Riis -- Correspondence; Fredericks, Carlton -- Correspondence; Hayes, Arthur Garfield -- Correspondence; Holmes, John Haynes, -- 1879-1964 -- Correspondence; Moore, Martha Riis -- Correspondence; Owre, J. Riis -- Correspondence; Riis, Jacob A. -- 1849-1914 -- Correspondence; Rorty, James, -- 1890-1973 -- Correspondence; Seldes, George, -- 1890-1995 -- Correspondence; Wallace, DeWitt, -- 1889-1981 -- Correspondence; United States; United States. -- Navy -- History -- World War, 1914-1918.; American Civil Liberties Union; Reader's Digest Association; Antitrust law; Automobile repair fraud; Cigarettes; Fraud; Smoking; Tobacco; World War, 1914-1918 -- Naval operations, American; Authors; Editors